The Relationship Of Family Support With The Quality Of Elderly Living In Sidomulyo Health Center Work Area In Pekanbaru Road - Bella Friska; Usraleli Usraleli; Idayanti Idayanti; Magdalena Magdalena; R Sakhnan (JURNAL PROTEKSI KESEHATAN, 2020)
Abstract Progress which occurs in health mainly gives impact on the increase in health quality, especially on the increase of life expectancy among elderly. Family is the main support system for elderly in terms of maintaining their health. The higher the family support, the better the quality of life of the elderly. In addition, quality of life is an indicator to evaluate the success of intervention on prevention and cure. The purpose of this research is to know relationship family support with quality of life of the elderly. Type of study is an analytic observational with cross sectional design. The population of the research is the whole of the elderly in the working area of the Sidomulyo Rawat Jalan Health Center Pekanbaru with a purposive sampling technique. Samples taken were 40 respondents. The independent variable is family support and the dependent variable is the quality of life of the elderly. The research data was taken using a questionnaire. This research was conducted in in the working area of the Sidomulyo Rawat Jalan Health Center Pekanbaru on march 21-25 2019. The result of Fisher’s test obtained p value (0,020) that’s means there is relationship family support with quality of life of the elderly. Therefore, the research can be used as information for the health center in the quality of family support involving elderly cadres to reduce the decline in the quality of life of the elderly. Abstrak Kemajuan di bidang kesehatan berdampak pada meningkatnya kualitas kesehatan serta meningkatnya umur harapan hidup terutama penduduk lanjut usia. Keluarga merupakan support system utama bagi lansia dalam mempertahankan kesehatannya. Dukungan keluarga yang tinggi akan meningkatkan kualitas hidup lansia. Kualitas hidup merupakan indikator untuk menilai keberhasilan intervensi dari segi pencegahan dan pengobatan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan dukungan keluarga dengan kualitas hidup lansia. Jenis penelitian yang digunakan adalah observasional analitik dengan rancangan cross sectional. Populasi dalam penelitian ini adalah seluruh lansia yang ada di wilayah kerja Puskesmas Sidomulyo Rawat Jalan Pekanbaru dengan teknik purposive sampling. Sampel yang diambil sebanyak 40 responden. Variabel independennya adalah dukungan keluarga dan variabel dependennya adalah kualitas hidup lansia. Data penelitian ini diambil dengan menggunakan kuesioner. Penelitian ini dilakukan di wilayah kerja Puskesmas Sidomulyo Rawat Jalan Pekanbaru pada tanggal 21-25 Maret 2019. Hasil uji Fisher’s didapatkan nilai p value (0,020) artinya terdapat hubungan dukungan keluarga dengan kualitas hidup lansia. Dengan demikian, penelitian ini dapat dijadikan sebagai informasi bagi pihak puskesmas dalam kualitas dukungan keluarga yang melibatkan kader lansia untuk mengurangi penurunan kualitas hidup lansia.